Intracytoplasmic Sperm Injection: Technical Improvement - Atsushi Yanaihara; Shinji Iwasaki; Momoko Negishi; Takashi Okai (Elsevier, 2005)
Successful fertilization using intracytoplasmic sperm injection (ICSI) was first reported in 1988 and the first successful ICSI pregnancy was in 1992. Since then, this technology has quickly become an indispensable technique in reproductive medicine, and its validity has been verified through several clinical studies over the past 10 years. After several technologic improvements, the rate of ICSI fertilization is comparable to that of conventional in vitro fertilization. In this article, we discuss how ICSI has improved fertilization and pregnancy rates.